PELATIHAN ENTERPRENEUR ENGINEERING DALAM MEMBANGUN JIWA WIRAUSAHA BAGI LULUSAN TEKNIK DI PROVINSI GORONTALO - Rifaldo Pido; Yohanes P erick; Rahmad Hidayat Boli; Mohamad Rifal; Eko Adityawan T. Zees (Batara Wisnu : Indonesian Journal of Community Services, 2021)
The purpose of implementing this Community Service program is to provide knowledge and skills insights for graduates about entrepreengineering, which can be used to demonstrate soft skills in the workplace or as a support in planning a project. This activity is carried out by providing training, including lectures, discussions, and simulations on the preparation of the Budget Plan (RAB) and Detail Engineering Drawing (DED). These targets and partners are alumni and users of work graduates such as consulting companies and contractors. The implementation of community service activities has been running according to the agreed plan. In the implementation process, this activity is carried out on an ongoing basis to implement the PKM program. This program has a lasting impact on preparing graduates who are excellent and ready to work